Fréquence d’utilisation de pratiques de gestion de classe selon la perception d’élèves du deuxième cycle du secondaire : la contribution majeure de l’expérience scolaire globale - Bernier, Vincent; Lagacé-Leblanc, Jeanne; Poulin, Isabelle; Ladouceur, Josiane (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
Many classroom management studies have documented teachers’ perspectives on their practices. However, the perspective of students, who witness these practices firsthand, has received relatively little attention. This research aimed to measure senior high school students’ perceptions of their teachers’ proactive and reactive classroom management practices, and to examine the contribution of personal (e.g., school experience) and environmental (e.g., grade level, school type, curriculum) variables. To achieve this, a quantitative research design was adopted and 278 students were recruited from four secondary schools to complete a self-reported online questionnaire. The results offer a novel perspective on the frequency of use of classroom management practices in Quebec high schools by presenting a portrait that is more preventive than reactive. They also highlight the major contribution of the quality of students’ school experience. The results also allow for the identification of avenues for intervention and research.